THE INFLUENCE OF THE MECHANISM OF GOOD CORPORATE GOVERNANCE AND CAPITAL STRUCTURE ON VALUE OF FIRM IN BANKING SUB SECTOR THAT WENT PUBLIC IN IDX IN 2010-2014 - Lasmanah, Lasmanah; Yuniar, Chintya Ratna (Jurnal Aplikasi Manajemen, 2017)
The purpose of this study to analyze the conditions and the influence of good corporate governance mechanisms are proxied by institutional ownership, independent commissioner and audit committee as well as the capital structure Debt Equity Ratio is proxied by the value of companies in the banking industry that went public during the 2010-2014 period. This study using purposive sampling and non-probability sampling technique with a total sample of 26 banks from 46 banks. The results showed that the joint mechanism of good corporate governance and capital structure provides weak influence on firm value. Hypothesis testing together shows that the mechanisms of good corporate governance and capital structure significantly affect the value of the company, while the partial mechanism of Good Corporate Governance provides a very weak influence the direction of positive correlation and significantly affect the value of the company. Then the capital structure provides a very weak influence the direction of the relationship is a negative and significant effect on firm value.